Discovery of potent, selective small molecule inhibitors of α-subtype of type III phosphatidylinositol-4-kinase (PI4KIIIα). Issue 16 (15th August 2015) - Raubo, Piotr; Andrews, David M.; McKelvie, Jennifer C.; Robb, Graeme R.; Smith, James M.; Swarbrick, Martin E.; Waring, Michael J.
Graphical abstract